Determinação da força de adesão através da técnica centrífuga entre partículas e membranas filtrantes - Almeida, Alcione Francisco de (Universidade Federal de São Carlos, 2013)
The study of micrometric and nanometric particle adhesion to surfaces have excelled in various technological fields. The adhesion has a significant role in the pharmaceutical industry, food, in the pneumatic conveying of materials in the manufacture of semiconductors, in the formation of aerosol, in painting, as well as environmental pollution and industrial hygiene. These studies are progressing to get a greater insight into the adhesion force between particles and surfaces. The main objective of this work is to check the influence of particle size of organic particulate material with the determination of the force adhesion between these particles and a substrate of organic origin. The substrates used were the filters ester-cellulose membranes, varying the porosity in 0.2 μm, 0.4 μm and 0.8 μm. The particulate material: activated coal and soot, varying the diameter of 11.1 -17 μm, 17.1-23 μm and 23.1-29 μm. To get the value of the adhesion force, was used the centrifuge technique, in which the adhesion force is equal in magnitude, but with the opposite sign to the centrifugal force required to detach the particles of the substrate. To obtain experimental data by centrifugal technique varied angular speeds of compression: 1000, 2000 and 5000rpm for angular speeds of detachment: 1000, 3000, 5000, 7000, 9000, 11000, 13000 and 14000rpm, using a microcentrifugal (MA -860, Marconi equipment) whose maximum speed rotation is of 14000rpm. The analysis of each system particulate material/ ester-cellulose membrane was made using an image analysis program (Image-Pro Plus 7.0), in order to verify the behavior of the particles attached to the substrate, through of the detachment of these particles after application of angular speed of compression and detachment. On data obtained by image analysis it was possible to determine the adhesion force between particles and the substrates, apresenting a profile log-normal percentage of adhered particles on adhesion force. For each systems analyzed particulate material/ester-cellulose membrane was the direct influence of variation of angular speed of compression (press-on) on the strength of adhesion, being possible to observe that the average diameter of the particles of particulate materials influence on surface membranes and detachment that the porosity of the surface of ester-cellulose membranes also influence the determination of the adhesion force. And, as a result of these analyses, it was possible to make a comparison between the experimental data and models of literature.
Keywords: Engenharia química; Ar - poluição; Van der Waals, Forças de; Adesão; Compressão e desprendimento de partículas; ENGENHARIAS::ENGENHARIA QUIMICA